(untitled) (GEOmedia, 2019)
January 23, 2019 was held at the British School at Rome (BSR) a meeting on Second World War military intelligence: aerial photography in the Mediterranean theater. Allan Williams, the main speaker, is the director of the National Collection of Aerial Photography (NCAP) Edinburgh, the dedicated archive to conservation and dissemination of the aerial photographic heritage in a time frame that ranges from the end of the nineteenth century to the present days. On this occasion, the emphasis was on that part of the collection consisting of aerial images taken from allied photo scouts in the context of the war in Europe.